Radiação solar em superfieies horizontal e vertical com exposição norte - Santos, J. M.; Simão, S.; Petta, A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
In the field of agrometeorological studies we are in need of the estimation of the solar radiation frequently. At the present study the authors have worked out some dat:t regarding the hours of sunshine during the months of August, September, October, November, December and January of 1957, 1958 and 1959. Based on such hours of sunshine in the Agrometeorological Station, located at the Escola Superior de Agricultura "Luiz de Queiroz" - U.S. P., in Piracicaba, the authors calculated the solar radiation received on a plane and horizontal surface, from the method proposed by Glover and Mc Culloch. With those results the authors estimated the percentual part of radiation that would be received on vertical wall facing north.